Effect of pH on Biosorption Ion Cd(II) in Solutions using Lengkuas Merah (Alpinia Gralanga) - Ahmad Faris Fauzi; Lisa Utami (Indonesian Journal of Chemical Science and Technology (IJCST), 2018)
The biosorption characteristic of Cd(II) ions from aqueous solution using Lengkuas Merah (Alpinia Gralanga) were investigated as a function of pH. The maximum biosorption capacity of a Lengkuas Merah (Alpinia Gralanga) for Cd(II) was found to be 18,37 mg/L and 91,85% at optimum pH was 10. At pH 2 to 10 the biosorption of Cd ions tends to increase. The result showed that the lengkuas merah  can be evaluated as an alternative biosorbent to treatment waste water containing Cd(II). A Lengkuas Merah is low cost and has considerable high biosorption capacity.